2012
DOI: 10.1002/app.38590
|View full text |Cite
|
Sign up to set email alerts
|

Lanolin‐based organogels as a matrix for topical drug delivery

Abstract: The current study deals with the development of lanolin‐based emulsion gels by hot emulsification method. Bright‐field, phase contrast, and fluorescent micrographs of the gels have shown the uniform distribution of circular water droplets in the formulations. Coalescence of water droplets was observed in gels containing higher proportion of water. Fourier transform infrared spectrophotometric studies indicated absence of Ln‐drug chemical interactions. X‐ray diffraction studies suggested an increase in amorphou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…The use of L2 and L3 organogels did not result in the formation of microparticles. This may be associated with the lower thermal stability of L2 and L3 organogels . In our previous study, we found that the L2 and L3 organogels were unstable when they were tested in a cyclic thermal test (−20–37°C).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The use of L2 and L3 organogels did not result in the formation of microparticles. This may be associated with the lower thermal stability of L2 and L3 organogels . In our previous study, we found that the L2 and L3 organogels were unstable when they were tested in a cyclic thermal test (−20–37°C).…”
Section: Resultsmentioning
confidence: 94%
“…The formation of organogel was predominantly influenced by the proportion of water. The stable organogels were formed when the lanolin : water proportion was maintained 2 : 1, 1 : 1, and 1 : 2 . Formation of organogels was checked by inverted tube method (Figure ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug release kinetics was studied using two different mathematical models viz., Higuchian model and KorsmeyerPeppas (KP) model (31).…”
Section: In Vitro Drug Release Studiesmentioning
confidence: 99%